Implementación de software libre para desarrollar el proceso de enseñanza y aprendizaje del atlas del cuerpo humano para los niños y niñas del séptimo año de Educación General Básica en la Unidad Educativa ¨Dr. Néstor Mogollón López¨ en el periodo lectivo 2016 - 2017. - Espinosa Villacres, Carlos Alberto (2017)
The present investigation was established in the implementation of free educational software, atlas of the human body, in the area of Natural Science, in the school “Dr. Néstor Mogollón López ", "in the community El Moral" in La Maná, province of Cotopaxi, in the students of the seventh year of basic education. The problem that has been identified through the surveys with the teacher and the thirty students was referring to the scarce technological resources; this failure was due to the fact that they did not have specific free educational software in the required area; In addition there was a need for training teachers and students in the use of technological resources. It was possible to identify the benefits of the free educational software of the atlas of the human body, through the research of the web source and books, to be used with the technological tools improving the teaching and learning process. This activity aroused interest with the students, to acquire new knowledge in the area of Science, especially to know the different parts of the human body, with 3D graphics and scientific contents. The software that we propose, has open codes that are free and available on the web, this saved economical resources. On the other hand it allowed to exercise the content and the interactive character; allowing to develop intellectual activities of observation, interpretation, comparison, schematization, reflexive critical thinking; Consenting to creativity in what was observed in a very entertaning and attractive way, this get the students motivated to use the technological resources in modern chairs.Teacher and student are trained on the use of technological tools improved the teaching-learning process in the school "Dr. Néstor Mogollón López ";obtaining positive results.